Dampak Putusan Mahkamah Konstitusi Nomor 90/PUUXXI/2023 (terhadap Hak Asasi Manusia dan Sistem Demokrasi di Indonesia) - Astuti, Widya; Siswi Enggarani, Nuria (Fakultas Hukum Universitas Islam Malang, 2025)
The establishment of a minimum age limit of 40 years for candidates for President and Vice President has sparked debate because it limits the participation of the younger generation. The impact of Constitutional Court Decision No. 90/PUU-XXI/2023 on human rights and the democratic system is still limited. This research aims to examine the impact of the decision on constitutional rights related to equality, non-discrimination, and political access. This research uses normative juridical research methods, with statutory and conceptual approaches. The results of this study found that the Constitutional Court Decision No. 90/PUU-XXI/2023 provided significant changes in expanding the access of experienced young people to run for office. However, the decision also raises concerns regarding the potential politicization of judicial institutions that could threaten the independence of the judiciary. Therefore, strict supervision and balanced policies are needed to maintain the rule of law and ensure a healthy and sustainable democracy.